Behavioral Changes in Cleansing Complete Denture among Elderly after Instructions through Video Educational Method - Niko Falatehan; Wilson Edric (Universitas Sam Ratulangi, 2022)
Abstract: Tooth loss experienced by elderly can be alleviated with complete denture usage. Good complete denture hygiene behaviour is achieved due to effective instructions from dentists. Generally, instructions are given verbally or written but they are often ineffective due to misunderstanding or being forgotten by patients. Educational video method can be used by dentists to enhance the complete denture hygiene instructions. This study aimed to determine the effect of instructions given through educational video method on the complete denture hygiene behaviours of the elderly. This was an experimental study with the one group pre and posttest approach. Respondents were elderly at Yayasan Bina Bhakti Nursing Home. Hygiene behaviour was measured using a questionnaire and data were processed with SPSS T-Wilcoxon test. Data collection was done twice with same respondents, before and after the instructions were given through video, with 3-week interval. The results showed that complete denture hygiene behaviour of the elderly at Yayasan Bina Bhakti Nursing Home was categorized initially as bad category, and improved to good category after the instructions were given through video. Better hygiene behaviour was found in the elderly respondents (60-74 years old). In conclusion, positive change in complete denture hygiene behaviour was observed in the eldery after instructions through video.Keywords: complete denture hygiene behavior; educational video method; elderlyÂ Abstrak: Kehilangan gigi yang dialami oleh lanjut usia (lansia) dapat teratasi dengan penggunaan gigi tiruan lengkap (GTL). Perilaku pembersihan GTL yang baik tercipta melalui pemberian instruk-si yang efektif dari dokter gigi. Secara umum pemberian instruksi dapat secara lisan dan tulisan, namun seringkali hal tersebut kurang efektif karena dapat disalahartikan dan dilupakan oleh pasien. Penggunaan metode edukasi video dapat dimanfaatkan oleh dokter gigi untuk menunjang pemberian instruksi kepada pasien lansia mengenai pemeliharaan kebersihan GTL. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian instruksi melalui metode edukasi video terhadap perilaku pembersihan GTL pada lansia. Jenis penelitian ialah eksperimental dengan one group pre and posttest design. Perilaku lansia diukur menggunakan kuesioner dan data diproses dengan SPSS uji T-Wilcoxon. Pengambilan data dilakukan dua kali pertemuan dengan individu yang sama, sebelum dan setelah menerima instruksi melalui video dengan interval waktu tiga minggu. Responden penelitian ialah lansia di Panti Werdha Yayasan Bina Bhakti. Hasil penelitian mendapatkan perilaku pembersihan GTL dari responden sebelum diberikan instruksi berada pada kategori buruk dan terdapat peningkatan menjadi kategori baik setelah diberikan instruksi melalui video. Perilaku yang lebih baik ditemukan pada responden elderly (60-74 tahun). Simpulan penelitian ini ialah terdapat perubahan perilaku pembersihan GTL pada lansia setelah diberikan instruksi melalui metode edukasi video.Kata kunci: perilaku pembersihan GTL; metode edukasi video; lanjut usia